Five Principles and Five Skills for Training Interpreters - Kornakov, Peter (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractThis article provides a brief description of a number of guided training exercises which are used with groups and which can be used by all students outside the classroom as part of their self-training. A number of techniques aiming to develop key skills essential for any interpreter are analysed. Some definitions, including intuition, attention, concentration, dominant hemisphere/ear preference are introduced in the article with regard to interpreting. The article aims to answer the questions of what we should teach future interpreters and what kind of skills we need to teach them. Specific training for each skill is described in detail. Future interpreters should practice some psycholinguistic exercises, taking into account the fact that a major part of the work depends on self-training.The instructor's role is to aid self-preparation, and to provide some useful guidelines and exercises that can be used outside the language laboratory, without an instructor or sophisticated equipment. Some basic differences and similarities in the training of simultaneous and consecutive interpreters are analysed.